Some problems and prospects of development of school economic education (Pedagogy of Higher and Secondary Education, 2012)
Kulíshov V. S. Some problems and prospects of development of school economic education.The article highlights modern trends of economic education and training in secondary school, and expressed some assumptions about the future development of this educational movement.
Keywords: economic education; school education in economics; market economics; curriculum; older profile school